Development of a Fast Onset Proton Pump Inhibitor: Comparison of Fixed-Dose Combination of Rabeprazole and Sodium Bicarbonate (YPI-011) to the Conventional Enteric-Coated Rabeprazole - Bae S; Kwon J; Lee MH; Yu KS; Lee S (Dove Medical Press, 2023)
Sungyeun Bae,1 Jihoon Kwon,2 Mi-Hye Lee,3 Kyung-Sang Yu,1 SeungHwan Lee1 1Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, Republic of Korea; 2Department of Statistics, APACE, Seoul, Republic of Korea; 3Yungjin Pharmaceutical Co., Ltd, Seoul, Republic of KoreaCorrespondence: SeungHwan Lee, Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, 101 Daehak-ro, Jongno-gu, Seoul, 03080, Republic of Korea, Tel +82-2-2072-1920, Fax +82-2-742-9252, Email leejh413@snu.ac.krPurpose: Proton pump inhibitors (PPIs) are the first-line therapy for gastroesophageal reflux disorder (GERD). Unlike conventional PPIs, non-enteric coated PPIs with antacid salt enable a faster acid suppression through the rapid absorption of the PPI. YPI-011 is a newly developed fixed-dose combination of a rabeprazole with sodium bicarbonate (NaHCO3). This study compared the pharmacokinetics (PKs) and pharmacodynamics (PDs) of YPI-011 to the conventional enteric-coated rabeprazole (Pariet®).Materials and Methods: A randomized, open-label, two-treatment, two-sequence crossover study was conducted with two different doses (10 and 20 mg) and 44 subjects in each group. They randomly received either a test or reference treatment for 7 days in the first period and the other treatment in the second period. Blood samples for the PK analysis were taken after the single- and multiple-dose. Intragastric pH monitoring for the PD analysis was implemented for baseline and after the single- and multiple-dose.Results: Gastric acid suppression evaluated by the percentage decrease from baseline in the integrated gastric acidity for a 24-hour interval after the multiple-dose was similar between the treatments in both dose groups. The systemic exposure of rabeprazole at steady state after the multiple-dose was also similar between the treatments in both dose groups. The time to reach the maximum rabeprazole concentration was faster in the test treatment. The PK-PD relationship of PPI is well known, and the faster absorption of rabeprazole resulted in a more rapid mode of action in acid suppression.Conclusion: The fixed dose combination of rabeprazole with NaHCO3 showed a faster absorption and consequently, a more rapid gastric acid suppression with a similar systemic exposure of rabeprazole at steady state compared to the conventional enteric-coated rabeprazole.Keywords: comparative pharmacokinetics/pharmacodynamics, intragastric pH monitoring, gastroesophageal reflux disease, immediate release